Bibliometric insights in advances of papillary thyroid microcarcinoma: Research situation, hot points, and global trends - Chen, Kefan; Wang, Zhongqing; Sun, Wei; Zhang, Dalin; Zhang, Ting; He, Liang; Zhang, Hao (Frontiers in Endocrinology, 2022)
Background: Thyroid cancer has been on the rise over the last decade. Papillary thyroid microcarcinoma (PTMC) accounts for more than half of all thyroid cancers. Micropapillary carcinoma of the thyroid is a common but non-fatal form of thyroid cancer. To better comprehend, nearly two decades of scientific outputs were analyzed and summarized using bibliometric methods in this study. Methods: Approximately 1098 publications from 2000 and 2021 were included in WoS database through systematic retrieval. The general information was characterized, and developmental skeleton and research frontiers were explored. CiteSpace, VOSviewer, and R, Tableau were used to evaluate and visualize the results. Results: A total of 1098 publications from across 75 countries were identified. The annual number of publications showed an increasing trend in the past 21 years. China, Korea, the United States of America (USA), Italy, and Japan made remarkable contributions to the research of PTMC. Thyroid was the most productive journal. Miyauchi Akira published maximum articles. The utmost productive institution was the University of Ulsan. Risk stratification, active surveillance, and thermal ablation garnered the attention of researchers leading to novel approaches in the clinical diagnosis and treatment of micropapillary thyroid carcinoma. Conclusions: This bibliometric study provides a comprehensive analysis of global productivity, collaboration, and research hotspots within PTMC field, which will aid in directing research toward PTMC in the coming years.